2015
DOI: 10.1371/journal.pone.0119759
|View full text |Cite|
|
Sign up to set email alerts
|

Surgical Management for Thoracic Spinal Tuberculosis Posterior Only versus Anterior Video-Assisted Thoracoscopic Surgery

Abstract: Study DesignA comparable retrospective study.ObjectTo compare the clinical outcomes of surgical treatment by posterior only and anterior video-assisted thoracoscopic surgery for thoracic spinal tuberculosis (TSTB).Method145 patients with TSTB treated by two different surgical procedures in our institution from June 2001 to June 2014 were studied. All cases were retrospectively analyzed and divided into two groups according to the given treatments: 75 cases (32F/43M) in group A performed single-stage posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Paraspinal abscess, if present, would be conquered by appropriate pressure washing and postural drainage. It would certainly be a good choice for some scholars to promote the removal of lesions by a thoracoscope [ 21 ]. In our study, all patients had no recurrence of TB.…”
Section: Discussionmentioning
confidence: 99%
“…Paraspinal abscess, if present, would be conquered by appropriate pressure washing and postural drainage. It would certainly be a good choice for some scholars to promote the removal of lesions by a thoracoscope [ 21 ]. In our study, all patients had no recurrence of TB.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were provided by Zeng et al (17), indicating that the anterior approach should be limitedly applied for severe cervicothoracic tuberculosis. Nevertheless, other authors commented that the posterior approach was associated with more effective deformity correction, and less complications and mortality than the anterior approach (2,5,21). Taken together, anterior and posterior instrumentation have their own surgical indications respectively and thus the selection of the surgical approach should be based on the specific requirements of different kinds of patients.…”
Section: █ Resultsmentioning
confidence: 99%
“…Among the 14 studies identified, 13 were retrospective studies, 2 3 4 5 6 7 8 9 10 11 12 13 14 and 1 was a prospective study. 15 All but 2 had had a high risk of bias, 4 15 class of evidence IV ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%